Monitoring of the ionosphere TEC variations during the 17th August 1999 Izmit earthquake using GPS data - Dogan, U.; Ergintav, S.; Skone, S.; Arslan, N.; Oz, D. (SPRINGER HEIDELBERG, 2011)
In this paper, we aim to determine a snapshot of previously unstudied ionospheric variations which were recorded in a two-week interval before and after a large earthquake of M 7.6 occurred on 17 August, 1999, in the Marmara region of Turkey. We detected ionospheric perturbations before the earthquake occurred using Global Positioning System (GPS) data received from the Marmara Continuous GPS Network (MAGNET). Pre-seismic ionospheric total electron content (TEC) anomalies were observed three days before the earthquake at sets of stations near the earthquake location, while post-seismic traveling ionospheric disturbances could not be detected. The ionospheric variability had a negative sign with an enhancement of about 8-10 TECU (1 TECU = 10(16) electrons/m(2)) relative to the non-distributed state of the ionosphere. The results show that this method will be a useful addition to the already-available continuous monitoring techniques in the region.
Keywords: Izmit earthquake; GPS; ionosphere; TEC; MAGNET; TOTAL ELECTRON-CONTENT; ANOMALIES; PRECURSORS; Geology